2002
DOI: 10.1042/bj3630793
|View full text |Cite
|
Sign up to set email alerts
|

Association of the 72/74-kDa proteins, members of the heterogeneous nuclear ribonucleoprotein M group, with the pre-mRNA at early stages of spliceosome assembly

Abstract: We have investigated the role played in precursor mRNA (pre-mRNA) splicing by the protein pair of molecular size 72/74kDa, which are integral components of a discrete subset of heterogeneous nuclear (hn) ribonucleoproteins (RNPs) named large heterogeneous nuclear RNP (LH-nRNP). This 72/74kDa pair of proteins has been shown to belong to the hnRNP M group, and are referred to as 72/74(M). By applying specific immunoprecipitation assays in a consecutive series of splicing reactions in vitro, the antigenic 72/74(M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Because the hnRNP C proteins do not shuttle between the nucleus and the cytoplasm, they are apparently released from newly matured mRNAs within the nucleus or at the NPC. The hnRNP M proteins bind preferentially to poly(G)-and poly(U)-rich mRNA sequences (8,39), and like the C proteins they have also been implicated in regulating pre-mRNA splicing (20). It is currently unknown whether the hnRNP M proteins exit the nucleus with mRNPs or whether they are released from newly matured mRNAs in the nucleus or at the NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Because the hnRNP C proteins do not shuttle between the nucleus and the cytoplasm, they are apparently released from newly matured mRNAs within the nucleus or at the NPC. The hnRNP M proteins bind preferentially to poly(G)-and poly(U)-rich mRNA sequences (8,39), and like the C proteins they have also been implicated in regulating pre-mRNA splicing (20). It is currently unknown whether the hnRNP M proteins exit the nucleus with mRNPs or whether they are released from newly matured mRNAs in the nucleus or at the NPC.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, Drosophila ovarian, embryonic and S2-cell Rump protein migrate with an apparent mobility of ~70 kDa, consistent with its calculated molecular weight of 67 kDa. Mammalian hnRNP M proteins have been implicated in splicing through their association with pre-mRNA at an early step in spliceosome assembly (Kafasla et al, 2002). Studies in Chironomus have shown that Hrp59 binds to pre-mRNA co-transcriptionally and remains associated with the RNA until it reaches the nuclear envelope, and recent analysis of the Drosophila S2 cell protein shows that it regulates alternative splicing of its own mRNA (Hase et al, 2006;Kiesler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The hnRNP M protein contains an unusual repeat region rich in methionine and arginine residues that resembles a component of the cleavage stimulation factor (CstF) involved in polyadenylation (13). Since hnRNP M is transiently associated with the pre-mRNA at early stages of spliceosome assembly (27), it may thus act concurrently with several other WW domain-associated splicing factors. We observed that hnRNP M overexpression enhances exon 6 inclu- 5 HEK 293 cells.…”
Section: Discussionmentioning
confidence: 99%